The Influence of Visual Branding Innovation and Facility Design on Customer Value - Maulini, Yul; Nugroho, Danang; Supriatna, Bambang; Alhadihaq, M. Yusuf; Haryati, Risna (Majalah Ilmiah Bijak, 2023)
The purpose of this research is to examine whether visual branding innovation and facility design have an impact on enhancing customer value, both concurrently and partially, at Unkl347 in Bandung. Customers are the driving force behind business competition, prompting entrepreneurs to strive for innovation to attract and compete for customers. This research employs a descriptive and verifiable approach, utilizing descriptive and verifiable research methods. The data is collected through observations, interviews, questionnaires, and persistent company data. Primary data is gathered from a sample of 100 respondents. The analysis method employed is path analysis. The findings of this study demonstrate that facility design exerts a greater influence than visual branding innovation on customer value. Therefore, it is advisable to maintain and enhance facility design, while visual branding innovation should be evaluated consistently considering customer opinions to advance company progress and profitability, ultimately achieving a competitive edge among various clothing entrepreneurs in Bandung.